2016
DOI: 10.24924/ijise/2016.11/v4.iss2/43.48
|View full text |Cite
|
Sign up to set email alerts
|

Ethnography in the Cyberspace: Problems and Prospects

Abstract: This paper outlines some of the issues involved in conducting ethnographic research in the Internet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In Malaysia, there have been several studies conducted within various CMC settings (Stapa & Shaari;Tay et al;2016;Rusli et al, 2018). However, most of these studies collected Manglish features found online and listed its lexical functions.…”
Section: Manglishmentioning
confidence: 99%
“…In Malaysia, there have been several studies conducted within various CMC settings (Stapa & Shaari;Tay et al;2016;Rusli et al, 2018). However, most of these studies collected Manglish features found online and listed its lexical functions.…”
Section: Manglishmentioning
confidence: 99%